Simulation of technical and economical efficiency indices for central directed heat supply systems with hot water boilers - Nikitin E.E. (General Energy Institute of the National Academy of Sciences of Ukraine, 2010)
It is observed that baseline conditions of municipal energetics are described by a variety of problems, the main of which are permanent rise in prices for natural gas, significant out- dating and low level of energy efficiency of the equipment, unsatisfactory quality of heat supply services, and also disconnection of individual consumers from the central directed heat supply systems.The analysis of work on technical and economical efficiency of heat supply systems was carried out. This analysis in particular showed that one of key issues is formation of fair pricing for energy resources.On the basis of the consideration of energy balance and thermohydraulic design of the central directed heat supply systems with hot water boilers running on natural gas, the methodology of correlation assessment between indices of economical and energy efficiency, prices for energy resources, engineering data and operational performance was developed.By the example of a simple heat supply system a numerical simulation of the impact of such factors as disconnection of individual heat consumers from a network, price for fuel, electric power and delivered heat energy, value of heat losses in the networks, specific length of heat networks and heat source efficiency for the indices of energy efficiency and profitability of heat energy generation was carried out. Critical values of influencing variables, which provide zero level of profitability of heat energy generation under existing prices for natural gas and electric power, were calculated.The results of the investigation can be used for carrying out technical, economical and financial analysis of different options for heat supply systems.